Pharmacotherapy of apnoea-free sleep disorders in patients with metabolic syndrome - O. V. Lyubshina; A. L. Vertkin; M. Yu. Maksimova (Кардиоваскулярная терапия и профилактика)
Aim. To evaluate the effectiveness and safety of zopiclone in apnoea-free sleep disorders among patients with metabolic syndrome (MS). Material and methods. The study included 60 patients with chronic cerebrovascular disease (CerVD) and MS (mean age 53,3±11,2 years). Zopiclone was administered in the dose of 7,5 mg once a day, 30 minutes before going to bed, for 21 days. Therapy effectiveness was evaluated by various subjective and objective sleep assessment methods. Results. After a zopiclone treatment course, all patients reported substantial improvement of sleep quality. These beneficial effects were explained by changing sleep architecture — the duration of sleep phases and stages (%). In particular, Stage 1 of slow sleep phase, the most affected at the pre-treatment level, was significantly reduced by 20 %, while Stage 2 of slow sleep phase increased by 14 % (p<0,05). Conclusion. Zopiclone therapy in CerVD patients with MS and apnoea-free sleep disorders substantially improved subjective and objective sleep parameters. Zopiclone could be recommended as a first-choice medication in MS patients with apnoea-free sleep disorders.